Evaluation of the Educational Programme of Character in the School of SD IT Ummi Aisyah - Hanum, Siti Hanifa; Nasution, Inom; Siregar, Nadia Sabrina; Nasution, Fina Safitri; Yasmin, Salsabila; Hasibuan, Denny Fitriani; Amelia, Faradillah; Zaki, Fadhil Ahmad (Pusdikra-Publishing.com, 2024)
Program evaluation is an assessment of the results of efforts to address and solve problems used in policies and programmes. Implementation Character Education aims to improve the quality of education leading to the process of achieving the formation of the character of the student in an integral, integrated, and balanced manner, according to the standards of competence of graduates. Character education evaluation is aimed at the cultivation of values within students and the renewal of a common lifestyle that appreciates individual freedom. This research aims to find out the evaluation of character education programmes at SD IT Ummi Aisyah. This research uses descriptive research methods with a qualitative approach. Evaluation of character education programmes is carried out to provide reinforcement, improvement and measure the successful implementation of the character education programme implemented by the educational organizers.